Potential of LUSI Mud as geopolymer material for artificial lightweight aggregate - Rafiza Abd Razak (School of Materials Engineering, Universiti Malaysia Perlis, 2015)
This study aimed to produce artificial lightweight geopolymer aggregate (ALGA) from LUSI mud using geopolymer method to be applied in the ordinary Portland cement (OPC) concrete.